Destination Image, Tourist Satisfaction and Loyalty in the Eco-Tourism Environment - ANIQOH, Nur Aini Fitriya Ardiani; SIHOMBING, Nikous Soter; SINAGA, Sarman; SIMBOLON, Sahat; SITORUS, Sunday Ade (Journal of Environmental Management and Tourism, 2022)
The purpose of this study is to investigate the image variable of tourist destinations, visitor satisfaction and loyalty of tourist visitors affect the decision variable of tourists to visit through moderating variables of tourist visitor attitudes. In this study, the independent variable is related to the behavior of tourist visitors, the variable is the image of the desired tourist destination, visitor satisfaction and visitor loyalty, while the dependent variable is the tourist's decision to visit, and the moderating variable is the attitude of tourist visitors. The research method used in this research is descriptive quantitative research method using path analysis.In this study the independent variable is related tothe behavior of tourist visitors, such as the image of the tourist destination that visitors want, visitor satisfaction and visitor loyalty, the dependent variable is the tourist's decision to visit, with moderating variable the attitude of tourist visitors. The data analysis uses AMOS 18, and the data taken is data on the number of tourist visits who visited ecotourism in Indonesia for 2016-2021 years. Partially variable image of tourist destinations,tourist visitor satisfaction and tourist visitor loyalty have a significant effect on the decision variables of tourists to visit ecotourism destinations throughout Indonesia and the attitude variable of tourist visitors to visit ecotourism throughout Indonesia, while simultaneously the variable image of tourist destinations,Tourist visitor satisfaction and tourist visitor loyalty indirectly have a significant effect on tourist decision variables to visit ecotourism destinations throughout Indonesia through the attitude of tourist visitors to visit ecotourism throughout Indonesia. Through the results of research that has been stated that to increase the willingness or attitude of tourist visitors to decide to visit an ecotourism destination, the destination must be able to improve its image well, improving the image of ecotourism destinations will be able to increase tourist visitor satisfaction, with increased satisfaction, visitors will loyal and frequent to visit ecotourism tourist destinations throughout Indonesia.